Maternal relationships within an Iron Age burial at the High Pasture Cave, Isle of Skye, Scotland. (October 2019) - Dulias, Katharina; Birch, Steven; Wilson, James F.; Justeau, Pierre; Gandini, Francesca; Flaquer, Antònia; Soares, Pedro; Richards, Martin B.; Pala, Maria; Edwards, Ceiridwen J.
Abstract: Human remains from the Iron Age in Atlantic Scotland are rare, which makes the assemblage of an adult female and numerous foetal bones at High Pasture Cave, on the Isle of Skye, particularly noteworthy. Archaeological evidence suggests that the female had been deposited as an articulated skeleton when the cave entrance was blocked off, marking the end of use of the site. Particularly intriguing is the deposition of disarticulated remains from a foetus and perinate close to the adult female, which opens the possibility that the female might have been the mother of both of the infants. We used shotgun genome sequencing in order to analyse the mitochondrial genomes of all three individuals and investigate their maternal relationship, and we report here, for the first time, complete ancient mitogenomes from foetal-aged bone fragments. While we could not exclude the possibility that the female was the mother of, or maternally related to, the foetus, we could definitely say that she was not the mother of the perinate buried alongside her. This finding is contrary to the standard archaeological interpretation, that women in such burials most likely died in childbirth and were buried together with their foetuses. Highlights: Rare Iron Age cave burial assemblage of an adult female with foetal remains. First report of complete ancient mitochondrial DNA sequences from foetal-aged bone fragments. Shot-gun sequencing and mitochondrial genome analysis for maternal lineage identification. Female could be excluded as being the mother of one the infants.